The Understanding a good choice of color in poster design for children / Ahmad Waffin Mohamad Saudin & Azlan Zainal - Ahmad Waffin, Mohamad Saudin; Azlan, Zainal (Universiti Teknologi MARA, Perak, 2018)
This paper is about investigating the misuse of color in poster design for children between aged 4 to 7. This paper reviews what scientific color that can attract children interest. This paper also explores the relation between color of poster and children's play behavior, and how this relation can be utilized by designers to promote design for children. Good poster color can also catch the eyes that see it. The data will be collected and analyze using a quantitative method. Researcher make a survey by giving different poster color to the children for intended to investigate their color chosen. This paper will benefit to graphic designers as guideline to help use the correct color of the posters for children.